2008
DOI: 10.1182/blood-2006-10-053371
|View full text |Cite
|
Sign up to set email alerts
|

NFAT but not NF-κB is critical for transcriptional induction of the prosurvival gene A1 after IgE receptor activation in mast cells

Abstract: IntroductionMast cells are potent effector cells displaying versatile functions during immune responses and as regulators of inflammation. [1][2][3] Many of these functions are executed via activation of the high affinity IgE receptor (Fc⑀RI) and subsequent release of regulatory factors stored in granules. 4 In addition, receptor stimulation initiates signaling cascades, which result in activation of specific genes encoding cytokines and growth factors. 5 In some cases, the activated transcription has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The predominant NFATc1/aA induction correlated well with an increased binding of NFATc1 to the P1 promoter. This is shown in ChIP assays in which the binding of NFATc1 and c2 to the P1 promoter was compared with the binding to the Il4 and Tnf promoters, two well-known NFAT targets (23,24), and the Bcl2a1a/A1 and Nr4a1/nur77 promoters, two putative NFAT targets (25,26) (Fig. 7B).…”
Section: Nfatc2 Andmentioning
confidence: 90%
“…The predominant NFATc1/aA induction correlated well with an increased binding of NFATc1 to the P1 promoter. This is shown in ChIP assays in which the binding of NFATc1 and c2 to the P1 promoter was compared with the binding to the Il4 and Tnf promoters, two well-known NFAT targets (23,24), and the Bcl2a1a/A1 and Nr4a1/nur77 promoters, two putative NFAT targets (25,26) (Fig. 7B).…”
Section: Nfatc2 Andmentioning
confidence: 90%
“…76,77 Recently, the mechanism of this prolonged survival has been linked to the NFAT-dependent transcription of the antiapoptotic Bcl2 family member gene A1/Bfl-1. 78 The antiapoptotic function of A1 has also been described in neutrophils and macrophages. [79][80][81] IgE crosslinking on mast cells leads to Ca 2ϩ flux followed by NFAT translocation and up-regulation of A1 expression, which may explain previous data indicating that increased Ca 2ϩ levels are beneficial to mast cell survival.…”
Section: Role Of the Nfat Pathway In Innate Immunity 1383mentioning
confidence: 99%
“…Ullerås et al [32] reported that Fc RI-mediated activation induced A1 gene expression, and it was regulated by the calcineurin/NFAT pathway. CsA was found to reduce Fc RI-mediated mast cells survival through inhibition of calcineurin/NFAT pathway and subsequent reduced A1 protein expression.…”
Section: Pimecrolimus Causes Mast Cells Depletion By Induction Of Apomentioning
confidence: 98%